Comparison of the Efficacy of D2 Gastrectomy Plus Liver Radiofrequency Combined With Chemotherapy Versus Chemotherapy Alone in the Treatment of Advanced Gastric Cancer With Unresectable Synchronous Liver Metastases: A Multicenter Randomized Controlled Trial Protocol - Wang, Weidong; Gao, Ruiqi; Yu, Pengfei; Mo, Zhenchang; Dong, Danhong; Yang, Xisheng; Li, Xiaohua; Ji, Gang (Frontiers in Oncology, 2022)
Background: Whether the patients who have advanced gastric cancer with unresectable synchronous liver metastases need surgical treatment is one of the controversial topics among surgeons. A recent study published on Lancet Oncology suggested that compared with chemotherapy alone, gastric resection combined with chemotherapy had no survival advantage for advanced gastric cancer with unresectable synchronous liver metastases. A limitation of this study was that gastrectomy for gastric cancers was restricted to D1 lymphadenectomy and no metastatic lesions were removed. Whether D2 gastrectomy plus liver radiofrequency plus postoperative chemotherapy could provide benefits to these patients is worthy of further confirmation by high-level evidence-based medicine. Methods/design: This study will investigate the efficacy of D2 gastrectomy plus liver radiofrequency plus postoperative chemotherapy compared to chemotherapy alone in a prospective, multicentre, randomized controlled trial that will enrol 230 patients who have advanced gastric cancer with unresectable synchronous liver metastases. The patients will be randomly divided into two groups: the test group (D2 gastrectomy plus liver radiofrequency plus postoperative chemotherapy, n=115) and the control group (chemotherapy alone, n=115). The patients' general information, past medical history, laboratory tests, imaging results, surgery details, and chemotherapy details will be recorded and analysed. The overall survival (OS) will be recorded as primary endpoints. The progression-free survival (PFS) and the total incidence of complications will be recorded as secondary endpoints. Discussion: This study is to establish a multicentre randomized controlled trial to compare the efficacy of D2 gastrectomy plus liver radiofrequency combined with postoperative chemotherapy versus chemotherapy alone.